ENDORSE INFLUENCERS, E-SERVICE QUALITY AND PERCEIVED EASE OF BUYING INTEREST THROUGH TIKTOK - Saputri, Rika Dwi; Rahmawan, Ginanjar (Manager : Jurnal Ilmu Manajemen, 2023)
This study aims to examine the role of influencer endorsements, e-service quality and perceptions of ease of buying interest through TikTok live streaming. The population in this study is adolescents and adults from the age of 15 years to over 30 years who use the TikTok application and have watched live streaming and shopped through the TikTok Shop feature. The sampling in this study amounted to 170 adolescents to adults, and used the purposive sampling method, then applied it with the Statistical Package for the Social Sciences (SPSS). The data analysis technique uses multiple linear regression analysis. Research shows that influencer endorsements, e-service quality, and perceived convenience have a positive and significant impact on buying interest through TikTok live streaming